The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1063/5.0096519
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and recent advances in super-resolution spectroscopy: Stochastic and disordered-based approaches

Abstract: Spectroscopic applications are characterized by the constant effort to combine high spectral resolution with large bandwidth. A trade-off typically exists between these two aspects, but the recent development of super-resolved spectroscopy techniques is bringing new opportunities into this field. This is particularly relevant for all applications where compact and cost-effective instruments are needed such as in sensing, quality control, environmental monitoring, or biometric authentication, to name a few. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Disorder is ubiquitous and can be found in a large variety of systems ranging from, e.g. fluid dynamics [1], diffusion processes [2] to solids [3,4], biology [5][6][7], spectroscopy [8,9], or towards simulations for quantum computing [10][11][12]. The field of ultracold gases provides a versatile tool for combining quantum gases with disordered systems [13], offering a highly controllable model system for a broad range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Disorder is ubiquitous and can be found in a large variety of systems ranging from, e.g. fluid dynamics [1], diffusion processes [2] to solids [3,4], biology [5][6][7], spectroscopy [8,9], or towards simulations for quantum computing [10][11][12]. The field of ultracold gases provides a versatile tool for combining quantum gases with disordered systems [13], offering a highly controllable model system for a broad range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Miniaturized spectrometers with advantages of portability and low cost and power consumption have attracted much attention due to their potential in advanced application scenarios, including wearable devices, hyperspectral imaging, and internet of things. Computational spectrum reconstruction based on a series of response-modulated photodetectors with a gradient bandgap is one of the most promising methods for achieving such miniaturized spectroscopy systems. For instance, Yang et al successfully demonstrate a miniaturized spectrometer at the scale of tens of micrometers using a single compositionally graded CdS x Se 1– x nanowire . Recently, halide perovskites have also been used in photodetectors for human visual-like spectrum projection, full-color detection, and multispectral recognition owing to their outstanding properties such as facile solution-process fabrication, excellent light harvesting coefficients, and tunable bandgaps. Xu et al demonstrated a miniaturized multispectral detector based on a composition-gradient perovskite microwire detector array, offering a response edge ranging from 450 to 790 nm .…”
Section: Introductionmentioning
confidence: 99%
“…SMLM relies on the random sparse excitation of fluorescent molecules inside a sample in the spatial domain to achieve the subpixel-precise localization of individual molecules, allowing the accurate reconstruction of objects with spatial resolution finer than that of imaging systems. Inspired by SMLM, Boschetti et al first extended this method to the spectral domain using a random laser (RL), thus developing stochastic optical reconstruction spectroscopy (STORS). The basic idea of STORS is to perform sparse sampling in the spectral domain, which has two primary requirements for illumination sources . The first is that the emission modes have an appropriate distribution over the spectrum (i.e., sparsity).…”
Section: Introductionmentioning
confidence: 99%